TRANSFORMATIONAL LEADERSHIP IN THE DEVELOPMENT OF A QUALITY CULTURE OF MADRASAH (Research Problems at MTs and MA Pondok Pesantren Rafah Bogor) - Nana Meily Nurdiansyah; Armai Arief; Ashabul Kahfi; Hudriyah Hudriyah (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
This study aims to analyze the Transformational Leadership Characteristics of the Head of Madrasah Tsanawiyah / Madrasah Aliyah Rafah and to analyze the development of Madrasah's Quality Culture. Many studies have been conducted by other researchers, this happens to transformational leadership that this leadership can have an impact on the educational institutions they lead. Moreover, the educational institutions in this study have revitalized the challenges and needs of the surrounding community, across provinces, or even the archipelago. This research is qualitative research using a phenomenological approach. Methods The data collection in this study used observation, in-depth interviews, and documentation studies. The results of this study indicate that there is a change in the status of recognition of educational institutions which was originally under the Ministry of Education and now has shifted direction to the Ministry of Religion based on various factors including; Factors of Leadership, Community Needs, and Quality Management to improve these educational institutions through various ways, one of which is collaborating with other educational institutions as partners, so that advanced, superior and competitive education can be realized and felt by Students and the Community.